Assessment of Traning and Development Practices in Xyz Gold Mines Limited (Xyzgml) In Ghana - Eduku, Francis; Annan-Prah, Elizabeth (Advances in Social Sciences Research Journal, 2015)
This study assessed the effectiveness of training and development (T&D) in XYZ Gold Mines Limited (XYZGML). The census method was employed as the study was targeted at 53 junior staff employees who participated in engineering training programmes between July to September 2009; and 9 direct supervisors. Questionnaires were used to collect data for the study. The findings indicate that knowledge and skills level of trained staff in terms of engineering principles, techniques and practices increased after the training programme. However, the results showed that supervisors failed to review their performance regularly and were also not provided the needed feedback to improve their performance. The absence of a recognition scheme to reward trained employees militated against the learning transfer. In spite of these challenges, the training led to significant and moderate improvement in employees’ job performance. The study recommends that XYZGML develops a detailed procedure on training transfer; design and implement both financial and non-financial recognition schemes to reward supervisors and trainees who consistently demonstrate the new knowledge and skills on the job; and ensure trainees and their supervisors sign training performance contract specifying performance standards and expectations.